(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Indian banking system has gone through significant transformationfollowing financial sector reforms. Several prudential, payment, integratingand provisioning norms have been introduced to improve efficiency and trimmingdown the NPAs‟ to improve the financial health of the banking sector. In thispaper we explore an empirical approach to the analysis of commercial banks’nonperforming loans (NPLs) in the Indian context. The empirical analysisevaluates as to how banks’ non-performing loans are influenced by three majorsets of economic and financial factors, i.e., terms of credit, bank sizeinduced risk preferences and macroeconomic shocks.